A Comparative Study on Tear Film Analysis in Patients Undergoing Photorefractive Keratomileusis, Sub Bowman’s Keratomileusis, and Femtosecond-assisted Laser in situ Keratomileusis - Harika Reddy; B. Shashidhar; V. Haritha (Delhi Journal of Ophthalmology)
Aim: To evaluate tear film stability, tear secretion, lipid layer thickness in patients undergoing Photo refractive keratectomy (PRK), Sub bowman’s keratomileusis (SBK), and femtosecond-assisted laser in situ keratomileusis (femto LASIK). Materials and Methods: The study design is a prospective and interventional study of subjects seeking refractive surgery over 20 years of age. The decision to use PRK or LASIK (SBK and femtosecond LASIK) was based on each patient’s corneal topography and refractive error. LipiView interferometer was used to assess (Tear science, Morrisville, NC) lipid layer thickness and blink rate (complete and incomplete), Schirmer test 1 to assess tear secretion, tear film break up time (TBUT) to assess tear film stability pre and postoperatively. Results: In our study, there was a statistically significant decrease in tear secretion (Schirmer’s 1) at 1 month postoperative period in all the three groups. No difference was noted at 1-week postoperative period in all the patients who had undergone corneal refractive surgery. A statistically significant decrease in TBUT was noted at 1 month postoperatively in LASIK group (SBK and femtosecond LASIK). There was a statistically significant decrease in lipid layer thickness (LLT) in Both eye (BE), partial and complete blink rate in Right eye (RE), and complete blink rate in Left eye (LE) at 1 month postoperative period in all the three groups. In our study, PRK group showed less statistically significant decrease in tear film parameters (Schirmer’s 1 in BE, partial BR in RE and complete Blink rate (BR) in LE) compared to SBK group (Schirmer’s 1 in BE, TBUT in BE, partial BR in BE, and LLT in BE) and FEMTO LASIK group (Schirmer’s 1 in BE, TBUT in BE, partial BR in LE) at the 1-month postoperative period. Conclusion: Among 63 patients (23 in each group), no significant difference in tear film parameters was noted at 1 week postrefractive surgery in all the three groups (PRK, SBK, and femtosecond LASIK). At 1-month postoperative period, there was a statistically significant difference in most of the tear film parameters in all the three groups compared to preoperative values stating that there was an alteration in tear film stability postcorneal refractive surgery, which was clinically insignificant as the patients are on topical lubricants and low dose steroid drops. Among the three groups, PRK group had less tear film disturbance compared to femtosecond LASIK and SBK group.